Ending statelessness for displaced children: Impact on early childhood education - Britta Rude (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2023)
Displaced children often face educational disadvantages in their host countries. Statelessness might be one of the factors limiting educational access, but research on this aspect is limited. In this paper, I leverage the introduction of birthright citizenship for Venezuelan children in Colombia to analyze the effect of ending statelessness on educational participation during early childhood. I employ a difference-in-discontinuity strategy that exploits a birthdate and policy cutoff to determine whether a Venezuelan child became eligible for birthright citizenship or not. I find that the reform has positive effects on the participation rates of children below six years old. I explain these results by demand- and supply-side factors faced by displaced parents and their children.
Keywords: I28; J13; J18; J15; 330; Government policy; children; public policy; economics of minorities